In situ identification of ecotypes chirimoya (annona cherimola mill) with potential business skills in Churubamba district – Huánuco - Gonzáles Pariona, Fernando (2017)
The present research work entitled “In situ characterization of ecotypes of cherimoya (Annonacherimola Mill.) With potentially commercial skills in the Churubamba District” located in the provinceand Region Huánuco, was to determine in situ overall objective ecotypes cherimoya (Annona cherimolaMill) with potentially marketable skills in the Churubamba District - Huanuco and specific objectiveswere: Identify the characteristics of the fruit of different ecotypes of cherimoya with potentiallymarketable skills and identify the characteristics of the tree of different ecotypes of cherimoya withhigh producibility .. the type and level of research was applied, descriptive, where the populationwas constituted by plants and the sample consisted of two fruits per ecotype cherimoya, from 7localities district Churubamba-Huánuco. At the following locations (Chullqui, Cuchurubamba, Cascay,Quechualoma, Tambogan low Vinchos and Pachabamba); where 10 accessions In situ cherimoya of many existing in the area were collected for presenting characteristics similar to cumbe prototype,considering the type of exocarp smooth, soft to small bumps depressions, and the following externaland internal characteristics of the fruits were evaluated cherimoya: fruit shape, color exocarp,exocarp type, size (diameter and length in cm.), fruit weight, flesh color, Brix, pH (potential ofhydrogen ions), oxidation, number of seeds, weight seeds and pulp ratio / seed. Of which 3 ecotypeswere selected to present external and internal characteristics similar to cumbe prototype. They were:: GPCM - 002, of the town of Chullqui; GPCM - 003 of the town of Churubamba and GPCM - 007,of the town of Cascay, showed very similar to the prototype Cumbe internal features, as the color ofthe fruit pulp were observed mostly whites and creams minority, with Brix content of 19.8% to 32.9;the pH (potential of hydrogen ion) of from 4.61 to 5.12 degrees of acidity in pulps without oxidationof the fruit, with a ratio pulp / 2.27 lower seed.